A Decade of Change in the Gendered Organizational Structure of Methamphetamine Markets in the American Midwest - Grundetjern, Heidi (The British journal of criminology, 2023)
While much research has documented the gendered organization of crime markets, the variability of gender-segmentation across crime has received limited attention. Analysing interview data from a study involving two cohorts of incarcerated women who used methamphetamine in rural Missouri, USA, 40 in 2009 and 40 in 2019, this study investigates the organizational properties of markets following a shift from local methamphetamine production to imported methamphetamine, ice. Properties of the ice market include amplified uncertainty, rationality, complexity, and professionalism, as well as a shifted modus operandi with common use of violence; properties contributing to heightened exclusionary practices and gendered stereotyping. The study provides evidence to Steffensmeier’s theory of variability of gender segregation in crime markets and shows the ramifications that policy changes can have.